A Review on Importance of Biodegradable Packaging for Foods and Pharmaceuticals - Shafi, Huma; Bajpai, Meenakshi (Current Nutrition & Food Science, 2023)
Everything we buy leaves a type of waste, particularly the packaging, which is thrown away when its contents are unpacked. One can hardly ignore the hazard plastic packaging poses to the environment. Plastic is a petroleum-based product that is a long128;term pollutant, it takes a very long time to degrade and is not fully biodegradable. The long-term development goals must incorporate protecting the environment and nonrenewable resources. Different review papers, research papers, books, book chapters, internet sources, and other relevant literature were used for writing this review paper. The finding of this review shows that in recent years, the interest of researchers has been evoked remarkably towards the development of packaging material in a more sustainable way. Biodegradable polymers such as starch, cellulose, Polylactic acid, Polycaprolactone, Polyhydroxyalkanoates, etc., have been modified to produce bio-based plastic films/materials which can replace petroleum-based plastic, thus reducing the environmental burdens associated with non-biodegradable and plastic products. Billions of tons of packaging waste are accumulating across the world and one should look for ways to incorporate materials that make less of an impact on the globe. The use of biodegradable packaging material is the solution to the problem of plastic waste accumulation as it is economically feasible and safe for our environment. Green or sustainable packaging will be possible only when eco-friendly packaging becomes a ‘must-have’ product feature.
Keywords: Bio-based plastic